Blunders/Mistakes in Postmortem Examination and Suggested Remedies (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
Word blunders and mistakes have different meanings. Blunder means clumsy or foolish mistakes, while mistake means an error of judgment. There is no scope of blunders/mistakes in forensic medicine. A medial practitioner must remember that his responsibility as a medical jurist is very great, for very often his is the only reliable evidence on which the liberty of life of an individual depends. How often do autopsy blunders/mistakes occur? None knows because there are no data collection centres at national as well as state level. We discuss three examples of such blunders/mistakes. In one case, uterus was reported ruptured but it was found intact, in second case the finding of hanging was described but cause of death was opined as strangulation and in third case the opinion was pressure over the neck. We can suggest many remedial measures but root cause of such blunders/mistakes is teaching, which is not practically oriented
Keywords: Blunders; Mistakes; Autopsy; Postmortem